Menganalisa Kualitas Perairan Melalui Kandungan Karbonat Pada Sedimen Dasar Muara Sungai Serang Kulonprogo - Benny Hartanto (Sekolah Tinggi Maritim Yogyakarta, 2018)
This research is a study on the waters quality observed through the content of carbonate and organic substance found in the bed sediment of Serang river estuary in Kulonprogo. The result of the research is aimed to provide the data about the content of carbonate and organic substance as well as the size of granule. Then, in turn, this result will help to monitor one of the waters quality parameters in that area, besides it will provide the consideration in running the business on fishpond cultivation. Research method applied in this research is a descriptive method and the data is administered explosively, whereas the sampling is done using the purposive sampling method. The analysis on carbonate and organic substance is conducted chemically on the bed sediment of the waters, and the granule analysis is done using sieve shaker whereas the analysis of sediment distribution in the location is done using 4 statistic parameters : mean, deviation standard, skweness and kurtosis. The result of the physical analysis indicates that bed sediment of Serang river in Kulonprogo consists of granular silt, silted very fine and sand. The highest content of carbonate is found for about 16% - 16,4% in coastal area, the estuary consists of 9,2% - 9,6% and the river consists of 9,1% - 9,8%. The highest content of organic substance is found in the estuary and the lowest is found in the coastal area, whereas the content of it in the river is between them. Rubbish and organic waste accumulated in the estuary influence the level of the organic substance content, however, as a whole the content of organic substance in the estuary is in the medium classification.